Addition of nanosilicas with different silanol content to thermoplastic polyurethane adhesives - Jose-Roberto, Vega-Baudrit (2005)
Three nanosilicas with different silanol contents were prepared by treatment of hydrophilic fumed silica with dimethyldichlorosilane. This treatment reduced the silanol content and produced the particle agglomeration of the nanosilicas. Thermoplastic polyurethane (TPU) adhesives containing nanosilicas were prepared and characterized by FTIR spectroscopy, differential scanning calorimetry (DSC), plate-plate rheology, dynamic mechanical thermal analysis (DMTA), transmission electron microscopy (TEM) and stress-strain testing. Adhesive strength was obtained from T-peel tests of PVC/polyurethane adhesive joints. The addition of hydrophilic nanosilicas favoured the degree of phase separation between the hard (i.e. isocyanate+chain extender) and soft (i.e. polyol) segments in the TPUs; the higher the silanol content on the surface of silica, the higher the degree of phase separation, and the crystallinity of the polyurethane (due to the soft segments) was also increased. Hydrogen bonds between the ester carbonyl groups in the TPU and the silanol groups on the silica surface were created and more favoured by increasing the silanol content. The tensile strength increased and the elongation at break of the polyurethane decreased by increasing the silanol content of the nanosilica. Addition of nanosilica increased the immediate adhesion of the polyurethane adhesives to PVC, irrespective of the silanol content on the nanosilica. The higher the mechanical and the rheological properties of the polyurethanes containing nanosilicas with different silanol content, the higher the final adhesive strength. © 2005 Elsevier Ltd. All rights reserved.